Substitution reaction of triphenylphosphine oxide with rare-earth metal phosphido methyl complexes. (8th April 2015) - Lv, Yingdong; Zhou, Jiliang; Leng, Xuebing; Chen, Yaofeng
Abstract : Rare-earth metal phosphido methyl complexes [L Ln(Me)P(H)Ar] react with triphenylphosphine oxide to give [L Ln(Ph)CH2 P(O)Ph2 ], indicating C(alkyl)–P bond formation and C(aryl)–P bond cleavage. Abstract : Rare-earth metal phosphido methyl complexes, [L Ln(Me)P(H)Ar] (L = [MeCN(DIPP)CHC(Me)(NCH2 CH2 NMe2 )] −, DIPP = 2, 6- i Pr2 C6 H3 ;1 : Ln = Sc, Ar = 2, 4, 6- t Bu3 C6 H2 ;2 : Ln = Sc, Ar = 2, 6- i Pr2 C6 H3 ;3 : Ln = Sc, Ar = 2, 6-Me2 C6 H3 ;4 : Ln = Lu, Ar = 2, 4, 6- t Bu3 C6 H2 ;5 : Ln = Lu, Ar = 2, 6- i Pr2 C6 H3 ), were synthesized and characterized. Complexes1–5 reacted with triphenylphosphine oxide (Ph3 P{O) to give [L Ln(Ph)CH2 P(O)Ph2 ] (Ln = Sc(6 ), Lu(7 )), by a mechanism that includes C(alkyl)–P bond formation and C(aryl)–P bond cleavage. The molecular structures of1, 3 and7 were determined by single-crystal X-ray diffraction. A pathway for the formation of6 and7 was suggested.